Social work and gerontogeriatric assessment: social screening in the Guillermina Loor de Moreno Gerontological Center - Giler Basurto, Juan José (2020)
The objective of the article was to determine the intervention processes of the interdisciplinary team in the gerontogeriatric evaluation of the residents of the Guillermina Loor de Moreno Gerontological Center. The work consists of two interrelated sections. The first describes the role of the Social Worker in the Gerontological Center (Gerontological Social Work) as leader of the interdisciplinary team. The second focuses on the gerontogeriatric evaluation obtained through the PIII (Comprehensive Individual Intervention Plan) carried out by the team's professionals, who act subject to the technical regulations of the MIES (Ministry of Economic and Social Inclusion). This allowed to better understand and process the intervention protocols in the field of the elderly. The descriptive methods - exploratory, bibliographic and inductive-deductive allowed to synthesize the information of each process, the interview technique facilitated acquiring relevant information in the care received by this vulnerable group, proposing protocols in praxis for a better understanding in the instruments of assessment. To conclude, the presence of the Social Worker in the gerontogeriatric assessment process is essential in understanding the results, since, due to social interference in the application of technical regulations, it minimizes and streamlines the protocol for obtaining the report of the social screening in older adults.